Hubungan Motivasi, Efikasi Diri dan Kondisi Psikologis Dengan Kepatuhan Diet Pada Penderita Diabetes Mellitus Tipe 2 - Angraini, Dian Isti; Ernawati, Tutik; Sari, Merry Indah; Harmaina (Jurnal Kedokteran Universitas Lampung, 2025)
ABSTRACT The prevalence of diabetes mellitus has increased over time. Patient compliance in taking medication and meal planning (diet) plays a very important role in the success of treatment and controlling blood glucose. The study aims was to determine the association between motivation, self-efficacy and psychological conditions with diet compliance in patients with type 2 diabetes mellitus. This study is an analytical observational study with a cross-sectional approach and conducted from April to October 2023. The research sample was 95 diabetes mellitus type 2 patients in the work area of ​​the Kalirejo Pesawaran Lampung Health Center. The sample was taken using a purposive sampling technique that met the inclusion and exclusion criteria. Data on motivation, self-efficacy and psychological conditions were taken using a validated questionnaire, and data on diet compliance was assessed by comparing food intake with the nutritional needs of patients with type 2 diabetes mellitus based on the 2x24h food recall questionnaire. Data were analyzed using chi square. The results showed that non-compliance diet in patients with type 2 diabetes mellitus was 80%. Motivation, self-efficacy and psychological condition are associated to diet compliance in diabetes mellitus patients (p=0.026; p=0.019; p=<0.001). Compliance with diet in type 2 diabetes mellitus patients is very necessary in controlling blood sugar in order to prevent complications. Motivation, self-efficacy and psychological condition of patients play an important role in diet compliance in type 2 diabetes mellitus patients.